ANTECEDENTS OF EMPLOYEE CREATIVITY AND ITS INFLUENCE ON JOB PERFORMANCE (Study on Police personnel at Surakarta Police Station) - Muhammad Nurrokhim; Intan Novela Qurrotul Aini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine the relationship between the antecedents of employee creativity and its effect on job performance in Police personnel in Surakarta Police Station. This research method uses quantitative methods with a total population of police personnel in Surakarta police station totaling 1083 personnel. The sampling technique of this study will refer to the criteria proposed by (Joseph F Hair et al., 2014) which are based on the Maximum Likelihood Estimation (MLE) technique. A good sample number according to MLE ranges from 100-200 samples, therefore the expected sample number is a minimum of 100 respondents and a maximum of 200 respondents (Joseph F Hair et al., 2014). Specifically for this study, the sample used was around 180-200 respondents at the Surakarta City Police Station. Data collection techniques use questionnaires that will be given randomly to the object of research. Data analysis tools using Smart-PLS applications. The results showed that Mindfulness has a significant effect on the creative process of members, Support perception of the organization has a significant effect on the meaning of work, Proactive personality has a significant effect on the meaning of work, Involvement of the creative process has a significant effect on employee creativity, Meaning of Work has a significant effect on employee creativity, Mindfulness has an indirect effect on employee creativity, in the mediation relationship First perception of support The organization has an indirect effect on employee creativity through the meaning of work, Both proactive personalities have an indirect effect on employee creativity through the meaning of work, Employee creativity has a significant effect on job performance. Keywords: Mindfulness, perception of organizational support, proactive personality, creative process involvement, work meaning, employee creativity, job performance